Designing The Structural Model of Students' Entrepreneurial Personality in Vocational Education: An Empirical Study in Indonesia - Kholifah, Nur; Kusumawaty, Ira; Nurtanto, Muhammad; Subakti, Hani (Journal of Technical Education and Training, 2022)
The importance of forming an entrepreneurial personality as a step to creating ideal entrepreneurial candidates through vocational education is still a significant obstacle. Currently, various theories and research studies reveal the role of digital literacy, interest in entrepreneurship and self-efficacy in shaping entrepreneurial personality. This study aims to examine the significant effect of digital literacy, interest in entrepreneurship, and self-efficacy on the entrepreneurial personality of vocational education students. In addition, self-efficacy was also tested as a mediator of the indirect influence of digital literacy and interest in entrepreneurship on entrepreneurial personality. Ex-post facto research with structural quantitative data approaches to examine as many as 597 vocational education students in the Province of Yogyakarta-Indonesia. Data collection was assisted using a closed questionnaire with a 4 Likert scale which had been tested for validity and reliability. Structural Equation Modeling is used to analyze the data through path analysis and bootstrap methods. The results of the path analysis show that digital literacy, interest in entrepreneurship, and entrepreneurial self-efficacy have a significant effect on entrepreneurial personality. In addition, a structural model that uses a mediator of entrepreneurial self-efficacy has also been tested significantly through bootstrap analysis with a confidence interval of 97.5%. Therefore, these results strengthen the theory that in shaping an entrepreneurial personality, digital technology literacy, interest in entrepreneurship and entrepreneurial self-efficacy are needed, so vocational education must strengthen these aspects.